Microwave Induced Synthesis of Some Novel Heterocycles From Substituted Chalcones - R. Deshmukh, Deepashree; Berad, B.N.; Raut, A.R.; W. Banewar, Vishal (Asian Journal of Chemistry, 2010)
Various substituted chalcones have been converted into 1,3,5-tri substituted pyrazolines. These pyrazolines have been obtained by reacting chalcones with isoniazide and thiosemicarbazide in stoichiometric proportion in microwave oven. The reaction mixture was irradiated within microwave oven for 1 min at 150 watt. The yields obtained with these techniques are higher and purity of compound obtained is better as compared to classical method of synthesis. The structures of all these pyrazolines Δ2 have been conformed on the basis of elemental analysis and spectroscopic data.